Pengaruh Rekrutmen dan Pelatihan Terhadap Kinerja Karyawan PT Senduk Jaya Internasional (Ekle’s Clinic) - Sindi Yoana; Henny Armaniah (Jurnal Riset dan Inovasi Manajemen, 2025)
PT Senduk Jaya Internasional (Ekles Clinic) is a company in the beauty and healthcare sector that views human resources as its primary asset. This research aims to analyze the impact of recruitment and training on employee performance. The research method used is multiple linear regression, with data collected through questionnaires, interviews, and literature studies.The results indicate that recruitment has a negative impact on employee performance, suggesting that an ineffective recruitment process can lead to decreased performance. On the other hand, training has a significant positive effect on employee performance, demonstrating that effective training can enhance employees' competencies and productivity. Simultaneous testing shows that both recruitment and training significantly influence employee performance. The coefficient of determination (R²) of 89.8% indicates that these two variables explain the majority of the variation in employee performance. By implementing a more selective recruitment process and continuous training, the company can improve the quality of its human resources and maintain its competitiveness in the beauty and healthcare industry.